Video error concealment: a brief presentation - Fernandes, Rui Vitor (2011)
Typical error control techniques are not very well suited for video transmission. On the other hand, video transmission over error prone channels has increased greatly, e.g., over IP and wireless networks. These two facts combined together provided the necessary motivation for the development of a new set of techniques (error concealment) capable of dealing with transmission errors in video systems. These techniques can be categorized according with the approach they take to solve the problem. This categorization is presented, describing the assumptions in which they are based and giving a few examples in each category. Finally, the advantages and disadvantages of each category are presented.